THD Improvement for a Multilevel DC-Link Inverter with Variable DC Voltage Sources - Alhassan M.; Singh S.K. (My University, 2025)
The Multilevel DC-Link Inverter (MLDCLI) is an important interface between solar panels and residential AC supply systems. In this paper, a MLDCLI using three asymmetric DC sources is designed to get a 15-level output voltage. This converter is controlled using a Simplified Gate Pulse Generation (SGPG) technique. Further, modified Nearest Level Modulation (mNLM) is applied to improve THD if there is a change in the ratio of DC voltage sources. To get the best value for THD, the gradient angles automatically change when the voltage in one of the DC sources changes. The results were verified using MATLAB and followed by experiments on a hardware prototype. © 2022 IEEE.